Advanced Joystick Algorithms for Computer Access Tasks - Dicianno, Brad E.; Mahajan, Harshal; Cooper, Rory A. (PM & R, 2015)
To compare 2 correction algorithms and 2 joysticks (a conventional movement-sensing joystick and a custom-designed isometric joystick) in computer access tasks. Repeated-measures, within-subject. National Veterans Wheelchair Games. Fifteen participants with various diagnoses including multiple sclerosis, spinal cord injury, traumatic brain injury, Wilson disease, and Parkinson disease. A computer access test scenario was used to evaluate the effects of applying proportional integral derivative (PID)–based and least means–based algorithms to suppress unintentional cursor motions by users with upper extremity spasticity. Trial completion time, reaction time, and trajectory-based measures: movement offset, movement variability, and percentage of out-of-path motion on test tracks. The quantitative outcome measures showed a high correlation with clinical measures for spasticity and functional independence. On small test tracks, compared to when no correction algorithms were used, both algorithms performed equally well in suppressing unintentional cursor motions. On longer test tracks, participants navigated most accurately while using the PID algorithm. Participants moved the cursor more accurately using the isometric joystick compared to the movement-sensing joystick, with only a slight increase in the task completion times. The joysticks and the advanced correction algorithms show promise for use in wide-ranging applications as control interfaces.